COVID-19 infections among HCWs exposed to a patient with a delayed diagnosis of COVID-19. (27th September 2020) - Baker, Meghan A.; Rhee, Chanu; Fiumara, Karen; Bennett-Rizzo, Carin; Tucker, Robert; Williams, Sarah A.; Wickner, Paige; Beloff, Jennifer; McGrath, Casey; Poulton, Alexa; Klompas, Michael
Abstract: We report on COVID-19 risk among HCWs exposed to a patient diagnosed with COVID-19 on day 13 of hospitalization. There were 44 HCWs exposed to the patient before contact and droplet precautions were implemented: of these, 2 of 44 (5%) developed COVID-19 potentially attributable to the exposure.